Controlling the dynamics of ultracold polar molecules in optical tweezers. (30th December 2021) - Sroczyńska, Marta; Dawid, Anna; Tomza, Michał; Idziaszek, Zbigniew; Calarco, Tommaso; Jachymski, Krzysztof
Abstract: Ultracold molecules trapped in optical tweezers show great promise for the implementation of quantum technologies and precision measurements. We study a prototypical scenario where two interacting polar molecules placed in separate traps are controlled using an external electric field. This, for instance, enables a quantum computing scheme in which the rotational structure is used to encode the qubit states. We estimate the typical operation timescales needed for state engineering to be in the range of few microseconds. We further underline the important role of the spatial structure of the two-body states, with the potential for significant gate speedup employing trap-induced resonances.